Higher education decision making of Australian women with caring responsibilities - Munro, Deborah; Willis, Jill; Gibson, Andrew; Laundon, Melinda (Frontiers in Education, 2023)
It is well established that women bear greater caring responsibilities than men, however little is known about how this care work influences the decision-making processes of female carers who are considering Higher Education (HE). These deliberations occur well before women commit to enrolling and frequently result in carers making decisions to delay or not pursue HE, with consequences for their own careers and the persistence of gender inequalities more broadly. A scoping review of academic literature published since 1980 which followed the PRISMA-ScR process for scoping reviews was conducted to answer the research question “What is the scope of the literature regarding the influence of caregiver responsibilities on Australian women’s tertiary education decision making processes?” Studying the literature in one national context enabled the influences of personal as well as contextual influences to be identified. The results show that very little is known about how women who have caring responsibilities make decisions about whether or not to undertake HE studies. Important issues were identified such as the lack of a clear definition of carer and recognition of this cohort as an equity group. A complex array of personal, cultural and structural factors which may enable women’s HE decisions were identified, including the desire to achieve personal life goals, the encouragement and support of family members and supportive workplaces. However, constraints such as competing time demands, the continuing prevalence of traditional gendered expectations and idealised notions of HE students as unencumbered were also noted. No studies directly addressed decision-making processes, or how the many elements combined to influence female carers prior to enrolment. The paucity of research points to an urgent need for studies which will address the gaps in knowledge. This review points to new directions in research and decision-making theories to encompass the role of context and care in decisions, and provides some advice meanwhile to inform career practitioners, HE providers and career researchers.